Digitalization of Customs Procedures: Current State and Prospects - Yereshko, Kateryna; Khoma, Olena; Pyslytsia, Anna (Journal of Vasyl Stefanyk Precarpathian National University, 2024)
The article is aimed at studying the current state of the digitalization of customs procedures in Ukraine and determining the prospects for the development of this process in Ukraine. Improving the electronic document management system at customs is consistent with Ukraine's European integration aspirations. Electronic declarations can not only minimize the time of customs procedures, but also fight corruption, develop international cooperation, and interact with the information systems of government organizations in the country. The purpose of the study is to determine the impact of the digital economy on the transformation of customs in Ukraine and to analyze the existing shortcomings of this system. The article describes the features and current state of digitalization of customs procedures in the context of simplification of customs control. The state of implementation of modern electronic services for the automation of customs procedures in Ukraine is analyzed. The authors emphasize the need for the development of world trade and the implementation of customs control procedures using communication technologies and electronic communications. The positive aspects of the introduction of information technology are identified. The achievements and problems of the process of reforming modern information technologies in the work of the State Customs Service of Ukraine within the framework of the strategic course of the state development are outlined. The reduction of customs clearance times can be achieved by introducing such new customs methods: 1) modern risk management processes using a multifunctional declaration system; 2) the widest possible use of post-clearance control methods; 3) gradual transition from transactional control to control based on audit methods; 4) independent control by participants of foreign economic activity over compliance with the law through the introduction of the institute of authorized economic operators. It is emphasized that the introduction of modern digital service technologies into the practice of the State Customs Service of Ukraine will improve the image of this state body both in Ukraine and in the international arena.